2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00178
|View full text |Cite
|
Sign up to set email alerts
|

Generative Adversarial Minority Oversampling

Abstract: Class imbalance is a long-standing problem relevant to a number of real-world applications of deep learning. Oversampling techniques, which are effective for handling class imbalance in classical learning systems, can not be directly applied to end-to-end deep learning systems. We propose a three-player adversarial game between a convex generator, a multi-class classifier network, and a real/fake discriminator to perform oversampling in deep learning systems. The convex generator generates new samples from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
75
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(75 citation statements)
references
References 38 publications
0
75
0
Order By: Relevance
“…After the seminal work proposed by Ian Goodfellow et al [1], GANs have been actively researched to generate realistic fake data. For example, many studies have used GANs for imitation [28][29][30]. BAGAN [2] addressed imbalance problems by coupling autoencoders and GANs.…”
Section: Gan-based Methodsmentioning
confidence: 99%
“…After the seminal work proposed by Ian Goodfellow et al [1], GANs have been actively researched to generate realistic fake data. For example, many studies have used GANs for imitation [28][29][30]. BAGAN [2] addressed imbalance problems by coupling autoencoders and GANs.…”
Section: Gan-based Methodsmentioning
confidence: 99%
“…Traditional oversampling techniques are usually employed after the feature extraction step in training data [63]. However, as DL algorithms utilize end-to-end feature extraction and classification, incorporating oversampling techniques with DL models would require costly parameter tuning [63], [64]. Furthermore, these techniques can work for low dimension tabular data but not for high-dimensional image data [65] [66].…”
Section: B Data Balancing Using Generative Adversarial Network (Gans)mentioning
confidence: 99%
“…Therefore, different data re-sampling techniques have been proposed by the researchers to balance the training data distribution. This is done either by over-sampling the minority class ( Mullick et al, 2019 ) or under-sampling the majority class ( Drummond et al, 2003 ). However, a recent study has shown that even models trained with balanced datasets amplify bias ( Wang et al, 2019 ).…”
Section: Related Workmentioning
confidence: 99%